(untitled) (Constructionism Conference Proceedings, 2025)
In the scope of the new technological era we live in, creative learning, prototyping and innovative problem solving are increasing in value day by day. However, newcomers in K12 laboratories find it quite challenging to take on new projects by themselves. Our observations in STEM projects and robotics competitions revealed a significant gap between theoretical knowledge and practical applications in mechanical systems. Aiming to find a constructive way to fill this gap, we prototyped kits labeled “automata”. Creativity can enhance the hands-on multidisciplinary learning experience by drawing interest in the process of creating a unique outcome[3]. The kits we designed in total have 6 models which we produce in our fablab consisting of a farm of 20+ 3D printers. The kits illustrate core concepts of cams, cranks and gears which are the most used and base of all mechanical systems. Each model has its own original design which illustrates systems we constantly face in our daily lives but fail to realize. When finalized with the design of the kits, to encourage innovative and creative thinking, we enhanced them with augmented reality (AR). As users interact with these models, movements are mirrored by corresponding AR animations on their mobile devices. For instance, geneva stop automata have jellyfishes rotating in correlation to the rotational movement of the gear. We had the opportunity to test this kit on K12 students, each workshop resulting with high accuracy of learning when comparing our before-after forms’ feedbacks. We believe this workshop is a great contribution to constructionist and innovative learning since by connecting physical building with digital visualization, the kit offers an interactive approach to learning mechanics, helping K12 students to bridge the gap between theory of mechanics and the practical technological application.